Penanggulangan Kasus Gizi Kurang dengan Intervensi Penyuluhan dan Pengukuran Antropometri di Desa Rugemuk Kecamatan Pantai Labu - Nadya Ulfa Tanjung; Fiyola Yoana; Rahayu M; Sahrul Amin; Tri D. A. Zega (FKM UIN Sumatera Utara Medan, 2021)
Medan is part of North Sumatra Province. The prevalence of undernutrition and malnutrition in Medan in 2013 was 19.3%, consisting of 4.2% malnutrition and 15.1% malnutrition. The prevalence rate is close to the national figure, which is 19.6%. Based on the 2015 MDGs target, the prevalence of malnutrition and children under five is 15.5%, this prevalence rate is included in the high category. The method used in this community service is counseling, demonstration and measurement of nutritional status. held on 6, 12 and 24 February 2020 in Rugemuk Village. The result of the service, namely counseling was carried out 3 times. It was conducted once at the Puskesmas Rugemuk Village, 2 times at the Posyandu Hamlet 1 and Hamlet III in Rugemuk Village, Pantai Labu District. From the results of the intervention and observations made, there are several children in Rugemuk Village whose nutritional status is less. Counseling is not only carried out at the Posyandu, but also students conduct counseling at the Rugemuk Village Health Center, Dusun II. Participants seemed satisfied with the holding of nutrition counseling with the theme according to the counseling target. Participants seemed enthusiastic when participating in nutrition counseling activities for each target group. The conclusion in this service is that intervention activities carried out to solve problems are counseling to the community as well as data collection and measurement of height and weight in children. All activities are carried out well and smoothly, outreach to the community as well as data collection and measurement of children's height and weight.